ODEcal: ordinary differential equation calculator by using MATLAB-GUI - Baki, Nur Afriza; Idalisa, Nur; Ghazali, Muhammad Hanif; Hussian, Nurul Hafawati Fadhilah; Fakhri, Imza (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
The ODEcal is an acronym for the Ordinary Differential Equations calculator. It is a standalone application developed using MATLAB App Designer to solve initial value problems of Differential Equations (ODEs) numerically. Initial value problems (IVPs) of ODEs are ubiquitous in science and engineering, as they model the behaviour of various phenomena over time. Solving IVPs of ODEs analytically can be challenging or impossible, especially for nonlinear or high-order systems. Therefore, numerical methods are often employed to approximate the solutions using discrete steps. This study creates an ODEcal for solving IVPs of ODEs, which is an application that implement various numerical algorithms and provide graphical and interactive features to help users explore and visualize the solutions. The interface of ODEcal in this study contains several methods comprising Euler, modified Euler, Runge Kutta of order four, and some MATLAB built-in function of ode113, ode45, ode23t, ode23s, ode15s, ode23tb and ode23.